The Perturbations of Drift in a Stratified World. (3rd October 2018) - Dixon, Deborah
Abstract : Though its 'Golden Age' in the nineteenth century has long since passed, Geology has recently been reanimated as a controversial and contentious subject, certainly, but also as an expert mode of knowing that provides a surety and confidence during a time of turbulence. The 'Anthro' prefix to Anthropocene debates has doubly implicated human beings as God-like agents of an exponential, carbon-fuelled planetary transformation but also as members of a precarious, Earthly species. Even as an anthropocentric 'forcing' of physical processes warms skies and oceans, and moves masses of material while laying down new sediments, human bodies are configured as future fossils to be laid on top of other Anthropocene boundary markers, from nuclides to chicken bones, in a globe-spanning Geologic archive. In this essay I do two things. First, I want to counter a predominant understanding of geologic materials, and geologized human beings, as necessarily sedimented in place, and thus helping to comprise a 'site'. I do so by delving into one of the key texts of a modernizing Geology, Murchison's (1839) The Silurian System. Drift, here, comprises unconsolidated sediments such as boulders, gravel, sand, silt and clay, that refuse to lie down quietly in taxonomic tables, cartographic keys or accounts of the site. Second, I want to demonstrate how this multiply caused, multi-directional, drift material presents us with another way of thinking about an Anthropocene, one which eschews a subterranean, stratified dramaturgy in favour of an exposed, irruptive, drifting geology that encompasses hydrocarbons from combustion engines as well as soot, grit and smoke. This is neither an archived geology, nor an anticipated future, but everyday living in and with drift.